2014
DOI: 10.1089/ten.tea.2013.0150
|View full text |Cite
|
Sign up to set email alerts
|

Successful Creation of Tissue-Engineered Autologous Auricular Cartilage in an Immunocompetent Large Animal Model

Abstract: Tissue-engineered cartilage has historically been an attractive alternative treatment option for auricular reconstruction. However, the ability to reliably generate autologous auricular neocartilage in an immunocompetent preclinical model should first be established. The objectives of this study were to demonstrate engineered autologous auricular cartilage in the immunologically aggressive subcutaneous environment of an immunocompetent animal model, and to determine the impact of in vitro culture duration of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 45 publications
1
47
0
Order By: Relevance
“…This increase in shear stiffness of the constructs can be due to formation of their net-like organized structure of the collagen type I and II fibers and increasing concentration of proteoglycans (45). In agreement with previous reports (9,46,47), the current results demonstrated that the expression of collagen II and Agg were up-regulated within silk, collagen, and gelatin scaffold after 8 wk implantation, compared with in vitro culture (Fig. 5).…”
Section: Discussionsupporting
confidence: 92%
“…This increase in shear stiffness of the constructs can be due to formation of their net-like organized structure of the collagen type I and II fibers and increasing concentration of proteoglycans (45). In agreement with previous reports (9,46,47), the current results demonstrated that the expression of collagen II and Agg were up-regulated within silk, collagen, and gelatin scaffold after 8 wk implantation, compared with in vitro culture (Fig. 5).…”
Section: Discussionsupporting
confidence: 92%
“…However, the samples exposed to standard medium contained very little type II collagen. Elastin fibres were present in both CCM groups at 12 weeks, albeit the elastin in the tissue‐engineered cartilage was still less dense than that observed in native auricular cartilage (Bichara et al , ). Considering the importance of elastin in native ear cartilage, the results above are very meaningful for the potential to engineer auricular cartilage.…”
Section: Discussionmentioning
confidence: 82%
“…A number of studies have demonstrated proof of principle for generating auricular cartilage using primary auricular chondrocytes and various scaffold materials (Xu et al , ; Bichara et al , ; Zhao et al , ). Some studies have extended these strategies by forming the auricular cartilage into the shape of the external ear (Cao et al , ; Zhou et al , ; Zhang et al , ; Otto et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated that the inflammatory response is primarily induced by biomaterials and/or their degradation products, regardless of whether they are biologically or artificially synthesized scaffolds [3, 4, 6]. Although collagen‐based cartilage was successfully engineered in the subcutaneous environment of an ovine model [7], it was suggested that the collagen was not adapted to engineering cartilage with specific shape and firmness because of its fast degradation. Polymer scaffolds, exhibiting predictable and reproducible mechanical and physical properties such as elastic modulus and degradation rate [8, 9], have drawn great attention in cartilage engineering.…”
Section: Introductionmentioning
confidence: 99%